Understanding Highly Pathogenic Avian Influenza outbreaks in Western Cape Ostrich industry: did network dynamics enhance vulnerability? Christine Moore. - Moore, Christine (Percy FitzPatrick Institute of African Ornithology, 2015)
Includes bibliographical references.